Brefeldin A—A Major Pathogenic Factor of Peanut Pod Rot from Fusarium neocosmosporiellum - Wang, Huiling; Wang, Xiaohan; Han, Huiling; Yu, Quanlin; Tan, Xinmiao; Liu, Junlong; Zhao, Yiting; Sun, Weiming (Toxins, 2024)
Fusarium neocosmosporiellum is the main pathogen of peanut pod rot in China. To investigate the type of F. neocosmosporiellum toxin and its pathogenic mechanism, a macrolide, brefeldin A, was isolated. The structure of the compound was identified by 1D and 2D nuclear magnetic resonance (NMR) and high-resolution electrospray ionization–mass spectrometry (HR-ESI-MS). At the same time, the content of the compound in healthy and diseased peanut capsules was detected, and its plant toxicity to radish, mung bean, rice, and peanut seed radicle elongation and pathogenicity to peanut pod rot were evaluated. The results showed that brefeldin A at 50 μg/mL could significantly inhibit the radicle elongation of rice seeds. Brefeldin A was detected only in pods with peanut rot. Injecting 2 mg/mL brefeldin A solution into peanut pods caused the severe decay of peanut pods at the R3R4 stage, which is consistent with the symptoms of peanut rot.